Disseminated herpes zoster in an Immunocompetent patient on long-term Clozapine: case report - Das, Nikhil; Hoque, Farzana (Bangladesh Journal of Medicine, 2023)
Disseminated herpes zoster is characterized by more than 20 herpetic lesions distributed across other body parts outside the affected dermatome. Disseminated herpes zoster occurs more frequently in immunocompromised patients and only a handful of case reports highlighted itsoccurrence in immunocompetent individuals. Clozapine use has been linked to decreased immune functioning, but no conclusive evidence to categorize clozapine as an immunosuppressive drug has been published. Here we report a case of a 65-year-old immunocompetent man on long-term clozapine who presented with vesicular lesions in a non-dermatomal distribution and was diagnosed to have disseminated zoster. Bangladesh J Medicine 2023; 34(3): 241-244